Computational control for strongly coupled structure, electric, and fluid systems. Issue 2 (4th March 2023) - Shankar, Vinay; Ramegowda, Prakasha Chigahalli; Ishihara, Daisuke
Abstract: Piezoelectric-structure interaction (PSI) and fluid-structure interaction (FSI) are multi-physics coupled systems. These interactions affect the vibration characteristics of coupled systems and thus such complex coupled systems must be controlled. This paper proposes computational control based on the finite element method for strongly coupled multi-physics analysis of the PSI of a thin flexible piezoelectric bimorph actuator. The vibration characteristics and the effect of direct velocity and displacement feedback (DVDFB) control in coupled systems are investigated. The displacement and velocity feedback gains are used together as well as separately. DVDFB control is extended to the FSI of stiff and soft structures to study vibration characteristics using active control and compare the stability of the two types of structure. The results of PSI show a reduction in actuator displacement amplitude and a shift in the resonance frequency due to DVDFB control. For FSI, the results for a stiff material show a reduction in displacement. The velocity feedback gain has no effect for a stiff material and leads to instability due to a large control force. The results for a soft material show a reduction in displacement and amplitude and more stability compared to the case for the stiff material.